Surface Modification Via Alginate-based Edible Coating For Enhanced Osmotic Dehydration Mass Transfer Of Ginger Slices - Muhammad Hafiz Hissham; Khadijah Hilmun Kamarudin; Aima Ramli; Mohd Ikmar Nizam Mohamad Isa (Horizon e-Publishing Group, 2024)
Indexed by Scopus